Tricuspid Annular Abnormalities in Isolated Left Ventricular Non-compaction—Insights From the Three-dimensional Speckle-Tracking Echocardiographic MAGYAR-Path Study - Nemes, Attila; Rácz, Gergely; Kormányos, Árpád (Frontiers in Cardiovascular Medicine, 2022)
Introduction. Prominent trabecular left ventricular (LV) meshwork and deep intertrabecular LV recesses are the main features of LV noncompaction (LVNC). The aim of the present study was to evaluate tricuspid annular (TA) morphological and functional abnormalities by three-dimensional speckle-tracking echocardiography in LVNC patients without right ventricular (RV) involvement. Materials and Methods. The present study consisted of 21 patients with isolated LVNC, from which 6 cases were excluded due to inferior image quality. The remaining patient group consisted of 15 subjects with a mean age of 52.1±11.4 years (9 males). LVNC was defined according to the Jenni’s criteria. Their results were compared to those of 21 age- and gender-matched healthy controls (mean age: 52.4±3.9 years, 14 males). Complete routine 2-dimensional Doppler echocardiographic examination was performed in all isolated LVNC patients and healthy controls. Results. Isolated LVNC patients showed significantly dilated end-systolic and end-diastolic TA diameter and area, which were accompanied with preserved TA functional properties and associated with right atrial (RA) volumes. Tricuspid annular plane systolic excursion (TAPSE) showed mild correlations with tricuspid annular fractional area change (TAFAC) and fraction shortening (TAFS). No correlations could be demonstrated between TAPSE and TA morphological and functional features. Extent of LV noncompaction did not correlate with any echocardiographic parameters. Conclusions. TA is dilated with preserved sphincter-like function in isolated LVNC patients. Longitudinal (TAPSE) and sphincter-like (TAFAC, TAFS) TA movements correlate with each other. TA dilation is associated with increased RA volumes respecting the cardiac cycle.